2021
DOI: 10.3390/ijms22116074
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anthocyanins and Iridoids on Transcription Factors Crucial for Lipid and Cholesterol Homeostasis

Abstract: Nutrition determines our health, both directly and indirectly. Consumed foods affect the functioning of individual organs as well as entire systems, e.g., the cardiovascular system. There are many different diets, but universal guidelines for proper nutrition are provided in the WHO healthy eating pyramid. According to the latest version, plant products should form the basis of our diet. Many groups of plant compounds with a beneficial effect on human health have been described. Such groups include anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Iridoids have been described as active compounds possessing significant cardiovascular, hypoglycemic, hypolipidemic, antihepatotoxic, choleretic, anti-inflammatory, antispasmodic, bioactivities [ 37 ], but their role in specific pathologies still needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iridoids have been described as active compounds possessing significant cardiovascular, hypoglycemic, hypolipidemic, antihepatotoxic, choleretic, anti-inflammatory, antispasmodic, bioactivities [ 37 ], but their role in specific pathologies still needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the same paper the authors reported that geniposide reduced ileal FXR-mediated reabsorption of bile acids, resulting in increased excretion of bile acids [ 40 ]. Gentiopicroside, in both acute and chronic alcohol induced mouse hepatosteatosis (the later stage of alcoholic liver disease, ALD) models, mitigated the upregulation of SREBP-1 and downregulation of PPAR-α, among others, by activation of AMPK [ 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previously published reports attempted to indicate the mechanism of action of CM fruit extract. It is well known that CM fruits are a rich source of biologically active compounds [ 6 , 9 ], with possible broad action within a single cell and the whole organism [ 30 , 31 ]. It is important to understand the mechanism of action of each individual compound of CM fruits, as well as the effect of the combination of compounds found in the whole fruit.…”
Section: Discussionmentioning
confidence: 99%
“…FABP1 was signi cant in the normal lipid metabolism of differentiated gut epithelial cells, especially the uptake and basolateral secretion of fatty acids 78 . Meanwhile, the CD36 receptor, as a multifunctional membrane receptor, effectively promoted the ability of fatty acid uptake and improved lipid metabolism 79 . Furthermore, a clinical study revealed that propionic acid and butyric acid could promote the formation of pig adipocytes and increase the expression of PPAR-γ, a transcriptional factor crucial for controlling lipid homeostasis 80 , as well as CEBPA mRNA in a stromal vascular fraction 77 .…”
Section: Discussionmentioning
confidence: 99%